Sex Difference in Global Burden of Major Depressive Disorder: Findings From the Global Burden of Disease Study 2019 - Li, Sangzi; Xu, Yufeng; Zheng, Leilei; Pang, Hu; Zhang, Qianni; Lou, Lixia; Huang, Xingru (Frontiers in Psychiatry, 2022)
Objectives: Globally, major depressive disorder (MDD) is considered to be a leading cause of disability. In this paper, we aim to investigate the sex difference in global burden of MDD by year, age, and socioeconomic development, utilizing disability-adjusted life years (DALYs). Methods: Global and national sex-specific DALY estimates caused by MDD from 1990 to 2019, and in different age groups were obtained from the Global Burden of Disease Study 2019. Human development index (HDI) was used as an indicator of national socioeconomic development. Spearman’s correlation and linear regression analyses were performed to explore the relationship between national socioeconomic development and sex difference in MDD burden. Results: Sex difference in global burden of MDD persisted between 1990 and 2019, with age-standardized DALY rates being 352 among males vs. 593 among females in 1990 and 354 vs. 564 in 2019. Females had higher burden of MDD than males at the same age. DALY numbers and rates among both sexes rapidly increased with age for those aged 10 to 24 years, along with gradually enlarging sex difference. Age-standardized DALY rates among females were higher than that among males for each HDI-based country group (P < 0.001). National age-standardized DALY rates among both sexes were negatively related to HDI. However, female to male age-standardized DALY rate ratios were positively associated with HDI (Spearman’s r = 0.383, P < 0.001; standardized β = 0.300, P < 0.001). Conclusion: Although some improvement in sex difference in global burden of MDD has been achieved, it still persists in the past three decades, with females bearing more burden than males. To reduce sex difference in global MDD burden, more attentions should be paid to young people and people in developed countries. The findings highlight the importance of making sex-specific health policy to manage mental impairment caused by MDD.